2016
DOI: 10.1186/s12916-016-0566-x
|View full text |Cite
|
Sign up to set email alerts
|

Interpreting whole genome sequencing for investigating tuberculosis transmission: a systematic review

Abstract: BackgroundWhole genome sequencing (WGS) is becoming an important part of epidemiological investigations of infectious diseases due to greater resolution and cost reductions compared to traditional typing approaches. Many public health and clinical teams will increasingly use WGS to investigate clusters of potential pathogen transmission, making it crucial to understand the benefits and assumptions of the analytical methods for investigating the data. We aimed to understand how different approaches affect infer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
131
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 129 publications
(134 citation statements)
references
References 75 publications
3
131
0
Order By: Relevance
“…75 A recent study of samples from a particular M. tb clone from KwaZulu-Natal in South Africa indicated that INH resistance ( katG ) mutations arose approximately 30 years earlier than RMP resistance. 76 A previous study from Argentina also placed katG mutations prior to rpoB ones, albeit with a much shorter (3 year) gap and overlapping confidence intervals.…”
Section: From Inh Resistance To Multidrug Resistancementioning
confidence: 99%
“…75 A recent study of samples from a particular M. tb clone from KwaZulu-Natal in South Africa indicated that INH resistance ( katG ) mutations arose approximately 30 years earlier than RMP resistance. 76 A previous study from Argentina also placed katG mutations prior to rpoB ones, albeit with a much shorter (3 year) gap and overlapping confidence intervals.…”
Section: From Inh Resistance To Multidrug Resistancementioning
confidence: 99%
“…The utility of WGS in retrospective outbreak analyses to more accurately identify clusters and true transmission events between patients has been well documented (20)(21)(22). Recent publications have described the potential of implementing WGS in a clinical setting for rapid resistance profiling of M. tuberculosis.…”
mentioning
confidence: 99%
“…These estimates may be even greater when considering longer duration infections, such as those of HIV negative individuals. While the thresholds chosen will depend on the mutation detection sensitivity unique to each study, the frequency of substantial within-patient distances adds weight to the mounting evidence 11,33,38,39 against ruling out epidemiological links on the basis of mutational thresholds between single samples.…”
mentioning
confidence: 99%